Model Penelitian dan Penjelasan Sejarah Sosial: Kelompok Reog sebagai Diaspora Warga Ponorogo di Jember tahun 1950-2005 - Suharto, Suharto (History Department, Faculty of Humanities, University of Jember, 2023)
Reog Ponorogo is one of the performing arts that characterizes the native people of Ponorogo. The cultural diaspora was experienced by Ponorogo’s group residents, who settled in Jember and established the existence of their original culture in their residence. This existentialist shows the emergence of the process of assimilation-structuralism. Using a field study approach accompanied by a literature review, this article will discuss and formulate research instruments and historical explanations from case studies of the establishment of reog groups by Ponorogo residents in Jember from 1950 to 2005. Keyword: Cultural diaspora; Formulate research; Historical explanation; Reog Ponorogo; Jember Residency